Structural analysis of code-mixing among Jordanians on Facebook - Alamaren, Eman; Shaidatul Akma Kasuma (Penerbit Universiti Kebangsaan Malaysia, 2022)
The main issue of the present aims at investigating the most frequent English categories that Jordanian students tend to use within Arabic discourse on Facebook. Furthermore, the study tries to examine the validity of Polack’s universal constraint ‘size of constituent' and whether Jordanian students tend to mix small constituents like nouns, verbs, adjectives, and adverbs, or they tend to mix large English constituents like clauses and phrases. To this end, a research design involves both quantitative and qualitative approaches was used. The quantitative analysis collected numeric information and used frequency distribution technique. On the other hand, the qualitative analysis collected qualitative data and used thematic analysis technique. The quantitative analysis revealed that Jordanian speakers generally insert both small and large English constituents in their speech; 70% of the inserted English constituents were small while large constituents constituted 29% of the constituents. That means, Jordanians tend to use small English constituents more than large ones. Particularly, nouns are the most frequently used mixed English constituents with (30 %), followed by adjectives which constituted 13% of the mixed English constituents. Accordingly, Poplack's universal constraint of size of constituent is violated. On the other side, the qualitative analysis of the data obtained showed that the size of the inserted English constituents has no effect on Arabic sentence structure and word order, that is, speakers form the sentence according to Arabic language and use constituents that have very limited grammatical restrictions. As a conclusion, Jordanian students use English nouns as the most frequently used English categories. Furthermore, the study provides a theoretical implication that is directed to the Arabic Language Academies in the Arab World. In fact, Arabic Academic are responsible to coin appropriate Arabic categories that meet the need of using English categories. That is, coining new Arabic categories will limit using English categories within Arabic discourse, save Arabic purity, and enrich Arabic language with new terms. Thus, Arabic language have to have new lexicon to develop and stay alive.